KLAUSA FORCE MAJEURE DALAM KONTRAK DAN PANDEMI COVID-19 DI INDONESIA - Kanzul Wafa; Irit Suseno; Endang Prasetyawati (Maleo Law Journal, 2020)
Some other policies related/to?COVID-19iiniIndonesia include "PP 21 years 2020 about large-scalepsocialprestrictions in accelerating the handling of2COVID-19", "Presidential decree 11 years 2020 on the determination of public health emergency COVID-19", and "Perppu 1 year 2020 on the country's financiallpolicykandpfinancial;system stability for the handling of COVID-19 The COVID-19 countermeasures and prevention policies affect the fulfillment of contracts, agreements, and business transactions. This is because some of these policies impede the process of fulfilling obligations in contracts, either directly or indirectly. The policy in question is primarily related to the closure of access, transportation or interaction. Methods used using normative research with orientation that is not sourced in the conceptual attitude that must be taken but also a combination of a rule of abuse which is a belief is fundamental. This belief is very important to produce an objective research result. Based on the freedom of agreement, the Corona COVID-19 pandemic virus is clearly expressed as a force majeure. However, if in the contract made Corona COVID-19 pandemic viruses are not included in the force majeure can be an issue, this is because the new Corona COVID-19 pandemic virus appears around the 2019 and in Indonesia itself has only gained its impact in the year 2020. This makes many contentious to determine whether the COVID-19 pandemic includes Force Majeure or not and whether this pandemic automatically cancels a contract that has been made and agreed upon by the parties.Keywords: force majeure; contract: pandemic